Impact of the "Thinking while Moving in English" intervention on primary school children's academic outcomes and physical activity: A cluster randomised controlled trial. (2020) - Mavilidi, Myrto F.; Lubans, David R.; Miller, Andrew; Eather, Narelle; Morgan, Philip J.; Lonsdale, Chris; Noetel, Michael; Karayanidis, Frini; Shaw, Kylie; Riley, Nicholas
Highlights: Physically active lessons significantly improved children's on-task behaviour. Active lessons enhanced literacy skills (i.e., grammar and punctuation but not spelling). Active lessons did not improve executive function skills or physical activity levels. Abstract: This study examines the impact of a classroom-based physical activity intervention on primary school students' academic outcomes and physical activity levels. Students (N = 283) from nine primary schools located in New South Wales, Australia were randomly allocated to a control (n = 5 schools) or Thinking while Moving in English (TWM-E) (n = 4 schools) conditions. Teachers delivered three 40-min physically active English lessons per week for six weeks. The control condition continued with the usual lessons. For both conditions, assessments occurred at baseline and post-test. The TWM-E group displayed improved on-task behaviour, and improved grammar and punctuation scores. Despite minimal effect on overall physical activity levels, active lessons have important benefits for students' on-task behaviour and literacy.